Implementasi PBL Berbantuan GSP Software Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematik Siswa - Evan Farhan Wahyu Puadi; Muhammad Irfan Habibie (IndoMath: Indonesia Mathematics Education, 2018)
This study aims to see the improvement of problem solving abilities of mathematical students of smp with the model of assisted PBL Geometer's Sketchpad, this study is quasi experimental because in this study subjects are not grouped randomly, but researchers accept the state of the subject as it aims to see the improvement of problem-solving skills and the ability of mathematical reasoning with PBL-aided model of Geometer's Sketchpad. The population of this study is all students of class VIII SMPN 2 Sindangagung Kuningan, the sample of the study is a class VIII students as much as two classes. The study consisted of two groups, the group with the learning of PBL with Geometer's Sketchpad and the group with conventional learning. Each group consists of thirty students. Research data were collected through problem-solving test, and observation. Data analysis is done qualitatively and quantitatively. Quantitative analysis was done by using t-test and nonparametric Mann-Whitney. Qualitative analysis is done by observing the observation data. From the plot diagram it can be seen that problem solving ability is increased in students with low category. The results of this study are (1) Improved problem-solving abilities that obtained a better learning model than students who received regular learning